Strengthening the STEM pipeline: impact of project-based synthetic biology program on high school students’ science identity and competency - Mims, Pamela J.; Lee, Lindsay E.; Kuldell, Natalie; Franklin, Chloe (Frontiers in Education, 2025)
This study investigates the impact of a project-based science education intervention, BioBuilderClub, on high school students’ science identity, self-beliefs, and content knowledge in synthetic biology. Addressing the critical “leaky pipeline” issue in biotechnology education, this intervention focused on fostering scientific engagement and competency through hands-on, interdisciplinary projects. Using descriptive and correlational statistics (i.e., paired t-tests, residual change regression), we found that the project-based intervention resulted in significant improvements in students’ self-perceived scientific engagement, competency, and content knowledge regardless of gender, locale, and first generation status. Across expert raters, we also found an improvement in the understanding of synthetic biology and students reported an increased interest in biotechnology and related fields. These findings underscore the potential of project-based learning to enhance STEM retention by building strong science identities, particularly among underrepresented groups. Future research should explore the long-term impacts of such interventions and their integration into standard curricula to further bolster the biotechnology pipeline.